PENGARUH PERIKLANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN THE ORIGINOTE EYE SERUM PADA SHOPEE DAN TIKTOK SHOP - Arifasari, Alfina Hidayatul; Rakhmawati, Dwi Yuli (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
This research aims to determine the effect of advertising and price on purchasing decisions for The Originote Eye Serum on Shopee and TikTok Shop. This type of research uses a quantitative approach. The population of this research uses all consumers who purchased The Originote Eye Serum in the city of Surabaya. The sample in this study used was 114 respondents using a porpuvise sampling technique. In this research, data collection used a questionnaire. In this research, the analysis technique used is multiple linear regression analysis using the SPSS version 22 application. The results of this research show that the advertising variable has an effect on purchasing decisions, the price variable has no effect on purchasing decisions, and advertising variables and price on purchasing decisions.